Generation of Approximate Weave Diagrams via Warp Pick Up Assignment (Journal of Fiber Bioengineering and Informatics, 2022)
Besides automatic looms in factories, looms for hand-weaving have also been used at home for producing handicrafts. Since the number of healds is small in rigid looms, it is necessary to pick up warp yarns by hand for each weft yarn. This operation is rather cumbersome when the sequences of warp yarns to be picked up are irregular. This paper proposes a method for generating approximate weave diagrams via warp pick up assignment. We represent the difference of weave diagrams in terms of tiling and image features to reflect their topological char-acteristics. Based on this representation, we propose a sequential re-assignment algorithm to generate approximate weave diagrams. The properties and time complexity of the proposed algorithm are reported. The proposed approach is validated in terms of the performance of the algorithm and woven fabric.
Keywords: rigid loom; hand weaving; weave diagram; approximation